MODELING LARGE-ANGLE PENDULUM OSCILLATIONS WITH QUADRATIC DAMPING AND DAMPING ON THE STRING - Pratama, Defrianto (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to find the right theoretical approach for real pendulum oscillations with large angles and include the air damping factor. Video of real pendulum oscillations were analyzed using Tracker software, to obtain experimental data. The real pendulum motion equation is modeled by a second order nonlinear differential equation by including linear damping, quadratic damping and damping on the pendulum string. The pendulum motion equation is solved by the 4th Order Runge-Kutta method then the results are compared with the experimental data. Modeling by considering quadratic damping and string damping is closer to the real phenomenon of pendulum motion than only considering linear damping.